Race, Crime, Intellectual Performance - and Food: Poor Nutrition Con-tributes to Racial Differences in Violence and SAT Scores - Gailliot, Matt (Advances in Social Sciences Research Journal, 2014)
Might differential nutrition contribute to racial differences in violent crime and intellectual performance (SAT scores)? Nutritional intake across the 50 states in the US differed by race, such that states with a higher percentage of Whites and a lower percentage of Blacks had poorer nutritional intake. Crime rates and SAT scores also differed by race, such that violent crime rates were higher in states with a lower percentage of Whites and a higher percentage of Blacks, and Whites scored higher and Blacks scored lower on the SAT than did other racial groups. Nutritional intake partially mediated the link between race and violent crime and fully mediated the link between race and SAT performance. These findings suggest that improving the diet of Black citizens may be a promising avenue toward reducing socially problematic racial disparities in crime and school.